ANALISIS PERBEDAAN MOTIVASI KERJA, LOYALITAS KERJA, DAN KINERJA GURU YANG BERSERTIFIKASI DENGAN YANG BELUM BERSERTIFIKASI - -, Margono -; -, Suprayitno - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2011)
ABSTRACT This study took place in SMK Pancasila. Its population is a vocational teacher Purwodadi Pancasila and the sample is the entire population of the 56 teachers. The purpose of this study was to 1) analyze the significance of differences in teachers certified and not certified in terms of the motivation of teachers in vocational Purwodadi Pancasila. 2) analyze the significance of differences in teachers certified and not certified in terms of employment in vocational loyalty Purwodadi Pancasila. 3) analyze the significance of differences in teachers certified and not certified in terms of the performance of teachers in vocational Purwodadi Pancasila. Results of data analysis, certified teachers tend to be more on work motivation high and moderate, but not yet certified teachers tend to be more on the low work motivation. While working on the loyalty of certified teachers tend to be more moderate and low, but not yet certified teachers tend to be more on the loyalty of high employment. And the performance of teachers who have been certified tend to be higher, but not yet certified teachers tend to be more on the performance of medium and low. Keywords: Job motivation, job loyalty, teachers performance